Procession Of Pujawali Mupuk Kembang At Pura Agung Banjar Adat Gegadon: Hindu Religion Edudcation Values - Ni Made Rai Setyawati; I Made Suastika; Made Iwan Indrawan Jendra (Institut Hindu Dharma Negeri Denpasar, 2018)
One of the ways taken by Hindu people to keep the harmony and prosperity in the world is by performing yajña. It is being exercised by krama Custom Banjar of Gegadon Kapal by conducting a ritual of pujawali at the Great Temple of Custom Banjar Gegadon. The temple is a small temple but enthroned by Ida Ratu Gede Sakti. The Pujawali is performed exactly on the day of budha kliwon wuku Pahang. This research discusses: (1) The form of procession of Pujawali Mupuk Kembang at the Great Temple of Custom Banjar Gegadon, Village of Kapal, District of Mengwi, Regency of Badung. (2) The function of procession practice of Pujawali Mupuk Kembang at the Temple (3) The Hindu religious education valuecontained in the procession.The theories being used in this research includ: 1) Structural functional theory, 2)Religious Theory, 3) Value Theory. The type of the research is descriptive qualitative. The primary sources for the data are congregation figures, religious figures andpublic figures, and its secondary sources are in the form of research results of books, articles, which are related with pujawali practice. The research instrument is interview guideline by using purposive technique, observation and documentation, the analysis technique, descriptive. The result of the research can be concluded as follows: (1) The procession of Pujawali Mupuk Kembang is a series of pujawali ritual from the beginning until the endwhich is closed with nyineb ceremony, (2) The function of pujawali consists of education, social, and religious function, (3) The values contained within pujawali procession is Hindu Religious education values namely tattva, ethic and ceremony.